The Origins of Materialism in India and Greece: Similarities and Differences - Sevilla Rodríguez, Martín (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Comparing sources for the history of primitive Indian and Greek materialism, the author indicates the similarities and differences that can be appreciated into the general characteristics of both philosophical tendences.